Implementasi Kriptografi Klasik ROT-13 untuk Pengamanan Data Teks Sederhana pada Sistem Informasi - Farah Putri Lestari; Agung Brastama Putra (Yayasan Sagita Akademia Maju, 2026)
Information security is an essential aspect in the management of information systems, particularly in protecting text data from unauthorized access. One basic security technique that can be applied is classical cryptography. This study aims to implement the classical ROT-13 cryptographic algorithm as a method for securing simple text data in an information system. The ROT-13 algorithm works by shifting each alphabetic character by 13 positions, producing encrypted text that cannot be directly understood. The methodology of this study includes system requirement analysis, design of the encryption and decryption processes, and implementation of the ROT-13 algorithm using the Python programming language. The results show that the system is able to perform text encryption and decryption correctly, where the original text can be accurately restored through the decryption process. Although the security level of ROT-13 is relatively low, the algorithm is effective for educational purposes and basic text data protection in information systems.